2009
DOI: 10.1161/circresaha.109.200451
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cardiac microRNA-Mediated Regulation Leads to Dilated Cardiomyopathy and Heart Failure

Abstract: RATIONALE Heart failure is a deadly and devastating disease that places immense costs on an aging society. In order to develop therapies aimed at rescuing the failing heart, it is important to understand the molecular mechanisms underlying cardiomyocyte structure and function. OBJECTIVE microRNAs are important regulators of gene expression and we sought to define the global contributions made by microRNAs toward maintaining cardiomyocyte integrity. METHODS AND RESULTS First, we performed deep sequencing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
278
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 334 publications
(293 citation statements)
references
References 60 publications
12
278
2
1
Order By: Relevance
“…The left and right ventricles of the heart were enlarged, and the ventricular wall was thinner in DGCR8 cKO mice (supplemental Fig. 1, B-D), which are similar to the findings described in mice with cardiac-specific knockout of DGCR8 (16). These observations are similar to what is clinically observed in end-stage heart failure, suggesting that the cKO embryos developed a cardiomyopathy-like condition.…”
Section: Conditional Deletion Of Dgcr8 In Vsmcs To Embryonicsupporting
confidence: 86%
See 1 more Smart Citation
“…The left and right ventricles of the heart were enlarged, and the ventricular wall was thinner in DGCR8 cKO mice (supplemental Fig. 1, B-D), which are similar to the findings described in mice with cardiac-specific knockout of DGCR8 (16). These observations are similar to what is clinically observed in end-stage heart failure, suggesting that the cKO embryos developed a cardiomyopathy-like condition.…”
Section: Conditional Deletion Of Dgcr8 In Vsmcs To Embryonicsupporting
confidence: 86%
“…Of 670 mouse miRNA probes in the array, after filtering out miRNAs with low signals, 218 miRNAs had detectable signals. 171 showed significant down-regulation, 16 were not significantly altered, and 31 were up-regulated specifically in DGCR8 cKO umbilical arteries. The array results indicated that the loss of DGCR8 leads to a global down-regulation of miRNA expression.…”
Section: Conditional Deletion Of Dgcr8 In Vsmcs To Embryonicmentioning
confidence: 88%
“…RNA editing in which adenosine is deaminated and thereby converted to inosine (I) has been reported for (Rao et al 2009) and newborn are mapped to the mir-133a-1 hairpin (top), and data from the ectopic expression assay are mapped to the indicated transfected hairpin (bottom). The lines indicate miR-133a.1 (dark blue) and miR-133a.2 (light blue), and red nucleotides indicate those that differ between mir-133a-1 and mir-133a-2.…”
Section: Rna Editingmentioning
confidence: 99%
“…Several in vivo and in vitro studies have shown that miRs regulate a myriad of cellular processes, including heart development and cardiac hypertrophy, both under physiological and pathological conditions (50)(51)(52)(53). Some important issues have been highlighted regarding the participation of miR in the process of pathological cardiac hypertrophy, since many targets can be regulated simultaneously or synergistically by one or more miRs, and miRs also can be regulated by molecular bases involved in cardiac hypertrophy and other processes, reinforcing or attenuating its phenotype (53)(54)(55).…”
Section: Micrornas Can Be Tiny Modulators Of Cardiac Hypertrophy Indumentioning
confidence: 99%
“…Nevertheless, there has been little investigation about miRs and physiological cardiac hypertrophy (51,57).…”
Section: Micrornas Can Be Tiny Modulators Of Cardiac Hypertrophy Indumentioning
confidence: 99%